2016
DOI: 10.1002/bio.3135
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy and molecular simulation on the interaction of caffeic acid with human serum albumin

Abstract: Fluorescence spectroscopy and molecular simulation were explored to study the interaction between caffeic acid and human serum albumin (HSA). The experimental results indicated that the fluorescence quenching mechanism between caffeic acid and HSA is a static quenching, which was proved again by the analysis of fluorescence lifetime by time-correlated single photon counting. The binding process is spontaneous and the hydrophobic force is the main force between caffeic acid and HSA. In addition, the binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The STD AMP factors showed that the molecular structure of each ligand affects the epitope mapping of each proton. Their preference for Sudlow site I as it was derived from the competitive STD NMR experiments confirms the existing literature data 46,49,59 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The STD AMP factors showed that the molecular structure of each ligand affects the epitope mapping of each proton. Their preference for Sudlow site I as it was derived from the competitive STD NMR experiments confirms the existing literature data 46,49,59 .…”
Section: Discussionsupporting
confidence: 87%
“…The best fitting model was the one binding site model supporting the STD NMR competitive results. Finally, a K a ¼ 1.17 Â 10 5 M À1 is reported for the BSA-salvianic interaction 49 again estimated with fluorescence spectroscopy. In our experiments the binding was too low to estimate the K a or the thermodynamic parameters using ITC.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Both free BSA and the AS-BSA complex demonstrated similar radii approximately 2.7 nm (Figure 2A and B), indicating that the compactness of BSA remained unchanged in the presence of AS. However, the fact that the RMSD value of the complex (Figure 2B) was slightly larger than that of the free BSA (Figure 2A) suggested that a synergic conformational change45 between AS and BSA might have occurred.…”
Section: Resultsmentioning
confidence: 98%
“…44 Both free BSA and the AS-BSA complex demonstrated similar radii approximately 2.7 nm ( Figure 2A and B ), indicating that the compactness of BSA remained unchanged in the presence of AS. However, the fact that the RMSD value of the complex ( Figure 2B ) was slightly larger than that of the free BSA ( Figure 2A ) suggested that a synergic conformational change 45 between AS and BSA might have occurred.…”
Section: Resultsmentioning
confidence: 98%